The Communication Strategy of Utilizing Fear of Missing Out (FoMO) to Popularize Padel at Padel Pro Kemang - Madelyn Aurelia Adaira; Made Leni Wijayanti Panggabean (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The rapid growth of padel in Indonesia, particularly among urban communities, has been closely associated with the emergence of Fear of Missing Out (FoMO), a phenomenon that encourages individuals to participate in activities perceived as popular and socially valuable. This study aims to analyze the communication strategies employed by Padel Pro Kemang in utilizing FoMO to popularize padel among upper-class communities in Jakarta. A qualitative descriptive approach was applied, with data collected through in-depth interviews involving Padel Pro Kemang management, coaches, influencers, and padel players. The findings indicate that Padel Pro Kemang strategically leverages FoMO through social media exposure, community development, event and tournament organization, social proof generated by high participation rates, and the construction of an exclusive image supported by premium facilities and international standards. These strategies successfully shape public perceptions of padel as a modern, prestigious, and socially desirable sport. The study further reveals that FoMO acts as an initial driver encouraging individuals to try padel, while long-term participation is sustained by positive playing experiences, health benefits, social networking opportunities, and a sense of belonging within the padel community. The findings demonstrate that FoMO-based communication strategies play a significant role in increasing public awareness, participation, and the popularity of padel among Jakarta’s urban upper-class society.